Interaction of Talaromyces marneffei with free living soil amoeba as a model of fungal pathogenesis - Pruksaphon, Kritsada; Nosanchuk, Joshua D.; Thammasit, Patcharin; Pongpom, Monsicha; Youngchim, Sirida (Frontiers in Cellular and Infection Microbiology, 2022)
Talaromyces (Penicillium) marneffei is an important dimorphic mycosis endemic in Southeast Asia and Southern China, but the origin and maintenance of virulence traits in this organism remains obscure. Several pathogenic fungi, including Cryptococcus neoformans, Aspergillus fumigatus, Blastomyces dermatitidis, Sporothrix schenckii, Histoplasma capsulatum and Paracoccidioides spp. interact with free living soil amoebae and data suggests that fungal pathogenic strategies may emerge from environmental interactions of these fungi with ubiquitous phagocytic microorganisms. In this study, we examined the interactions of T. marneffei with the soil amoeba Acanthamoeba castellanii. T. marneffei was rapidly ingested by A. castellanii and phagocytosis of fungal cells resulted in amoeba death after 24 h of contact. Co-culture also resulted in a rapid transition for conidia to the fission-yeast form. In addition, well-established virulence factors such as melanin and a yeast specific mannoprotein of T. marneffei were expressed during interaction with A. castellanii at 37°C. Our findings support the assumption that soil amoebae environmental predators play a role in the selection and maintenance of particular features in T. marneffei that impart virulence to this clinically important dimorphic fungus in mammalian hosts.